“Saya tidak mau mati sia-sia”: Pengalaman hidup mantan tahanan politik 1965–1966 di Indonesia - Hidayat, Muhammad Miftahul (Jurnal Psikologi Ulayat, 2025)
This study aims to fill a gap in the existing literature by examining the lived experiences and resilience of survivors of 1965–1966 political prisoners in Indonesia. Using a phenomenological approach, the research explores in depth how survivors cope with past traumatic experiences. The study was conducted over the course of one month in Jakarta, utilizing in-depth interviews, participartory observation within the Kamisan Action movement, and the collection of relevant documentary materials. The findings reveal that social movements can create spaces for memory preservation and resilience building. Participants' involvement in activism, such as Aksi Kamisan, not only strengthens personal resilience, but also fosters a sense of collective agency that challenges oppressive political systems and structures. Furthermore, this research highlights the importance of exploring the role of collective memory and social activism in building resilience, particularly in contexts where survivors of political violence are actively involved in shaping historical narratives.